2020
DOI: 10.1039/d0fo01362e
|View full text |Cite
|
Sign up to set email alerts
|

Modification of protein structures by altering the whey protein profile and heat treatment affectsin vitrostatic digestion of model infant milk formulas

Abstract: The aim was to investigate how protein structures in model infant milk formulas affect proteolysis kinetics during in vitro digestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 65 publications
(76 reference statements)
5
21
1
1
Order By: Relevance
“…At the end of the in-vitro gastric processing, the residual intact protein matter (normalised to t = 0 min) accounted for 10.1, 24.0, and 27.0% in the case of total caseins, β-lactoglobulin and α-lactalbumin, respectively. These values are generally in accordance with previous studies, confirming that caseins are more susceptible to pepsinolysis than whey proteins ( Halabi et al, 2020 , Phosanam et al, 2021 ). Even though native whey proteins are generally recognised for their substantially higher intragastric peptic resistance ( Borreani et al, 2016 ), the implementation of thermal processing is known as impacting proportionally to its severity the pepsinolytic breakdown of whey proteins ( Barbé et al, 2014 , Macierzanka et al, 2012 , Peram et al, 2013 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…At the end of the in-vitro gastric processing, the residual intact protein matter (normalised to t = 0 min) accounted for 10.1, 24.0, and 27.0% in the case of total caseins, β-lactoglobulin and α-lactalbumin, respectively. These values are generally in accordance with previous studies, confirming that caseins are more susceptible to pepsinolysis than whey proteins ( Halabi et al, 2020 , Phosanam et al, 2021 ). Even though native whey proteins are generally recognised for their substantially higher intragastric peptic resistance ( Borreani et al, 2016 ), the implementation of thermal processing is known as impacting proportionally to its severity the pepsinolytic breakdown of whey proteins ( Barbé et al, 2014 , Macierzanka et al, 2012 , Peram et al, 2013 ).…”
Section: Resultssupporting
confidence: 92%
“…The hydrolysis progress of the milk proteins was monitored by quantifying the amount of primary amino groups present in the collected food matrix, and gastric and small intestine chymes using the O-phthaldialdehyde (OPA) method of Halabi, Croguennec, Bouhallab, Dupont, and Deglaire (2020) . The food matrix was diluted 50-fold, whilst the gastric and small intestine phases were diluted 25 times.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, heat-induced denaturation caused by intense thermal processing promotes digestion of milk proteins [ 186 , 201 , 202 ]. For instance, digestion of caseins in infant formulas heated at 80 °C was faster than the digestion of the unheated counterpart, which could be explained by their smaller micelles covered by denatured whey protein aggregates, thus increasing the accessibility to proteases [ 203 ]. Further, another study showed that upon more intense temperatures of 120 °C, caseins were even more rapidly digested than after pasteurisation at 82 °C [ 204 ].…”
Section: Cow’s Milk-based Infant Formulasmentioning
confidence: 99%
“…The calculation of DH was outlined previously (Sheng et al, 2021). The maximal concentration of free amines was obtained by hydrolyzing the protein solutions before digestion in 6 M HCl at 110°C for 24 h (Halabi et al, 2020;Sousa et al, 2020).…”
Section: Degree Of Hydrolysismentioning
confidence: 99%